Runtime Procedure for Energy Savings in Applications with Point-to-Point Communications - Sundriyal, Vaibhav; Sosonkina, Masha; Gaenko, Alexander (Anais do International Symposium on Computer Architecture and High Performance Computing (SBAC-PAD), 2012)
Although high-performance computing has always been about efficient application execution, both energy and power consumption have become critical concerns owing to their effect on operating costs and failure rates of large-scale computing platforms. Modern microprocessors are equipped with the capabilities to reduce their power consumption using techniques such as dynamic voltage and frequency scaling (DVFS) and CPU clock modulation (called throttling). Without careful application, however, DVFS and throttling may cause a significant performance loss due to system overhead. This work presents design considerations for a runtime procedure that dynamically analyzes blocking point-to-point communications, groups them according to the proposed criteria, and applies frequency scaling by analyzing both communication and architectural parameters without penalizing the performance much. Experiments, performed on NAS parallel benchmarks verify the proposed design by exhibiting energy savings of as much as 11% with a performance loss as low as 2%.